Interferometric Sea Ice Mapping with TanDEM-X: First Experiments - Scheiber, Rolf; De Zan, Francesco; Prats, Pau; Sant’Anna Araújo, Laís; Künemund, Maren (2011 IEEE International Geoscience and Remote Sensing Symposium, 2011)
In summer 2010 during the commissioning phase of TanDEM-X, the TerraSAR-X/TanDEM-X constellation was operated in the pursuit monostatic mode allowing alongtrack interferometric measurements with very short time separation of only 2.6 sec. This paper presents first evaluations of data acquired on arctic sea ice scenarios and investigates the potentials for the mapping of ice sheet dynamics with respect to rotation and translation with this unique constellation. Due to the larger coverage, the data analysis is focused on interferometric ScanSAR data.